“A superstitious respect for the soil”? : environmental history, social identity and land ownership – a case study of forced removals from Lady Selborne and their ramifications, c.1905 to 1977 - Kgari-Masondo, Maserole Christina (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (History))—University of Stellenbosch, 2008.